2007
DOI: 10.1021/ef0701687
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CaO-Based Synthetic CO2Sorbents under Realistic Calcination Conditions

Abstract: Several concepts to capture CO 2 in power plants and hydrogen generation plants are under development using CaO as regenerable sorbent. The drastic decay in sorbent capture capacity of CaO obtained through calcination of natural sources of CaCO 3 (limestones or dolomites) justifies the search of synthetic sorbents that aim to overcome this decay in capture capacity. We have reviewed some of the recent literature on the subject and tested some of the proposed sorbents under comparable conditions. Our results co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 22 publications
3
57
0
Order By: Relevance
“…The direction of these research efforts can be categorized into four different strategies, (1) techniques using rigid supports, (2) use of additives (3) preparation of nanoparticles, and (4) use of different synthetic precursors. [131] The first method is based on the concept of employing a rigid porous material as a carrier or a matrix for the calcium oxide species. For example, Feng prepared very fine calcium oxide particles in an inert porous alumina support that preserved a high conversion of over 90 % after 9 cycles of carbonation and decarbonation ( Figure 25).…”
Section: Calcium Oxide Structural Modifications To Improve Adsorbent mentioning
confidence: 99%
See 3 more Smart Citations
“…The direction of these research efforts can be categorized into four different strategies, (1) techniques using rigid supports, (2) use of additives (3) preparation of nanoparticles, and (4) use of different synthetic precursors. [131] The first method is based on the concept of employing a rigid porous material as a carrier or a matrix for the calcium oxide species. For example, Feng prepared very fine calcium oxide particles in an inert porous alumina support that preserved a high conversion of over 90 % after 9 cycles of carbonation and decarbonation ( Figure 25).…”
Section: Calcium Oxide Structural Modifications To Improve Adsorbent mentioning
confidence: 99%
“…[141] Similarly, Grassa indicated that synthetic precursors including CaA C H T U N G T R E N N U N G (CH 3 COO) 2 , CaC 2 O 4 , and Ca(OH) 2 , produced adsorbents with little differences in adsorbent regenerability from natural limestones, if tested under realistic calcination conditions ( Figure 26). [131] 2.2.1.6. Magnesium oxides Besides calcium oxide, other alkaline earth metal oxides such as magnesium oxide have been investigated as adsorbents for CO 2 .…”
Section: Calcium Oxide Structural Modifications To Improve Adsorbent mentioning
confidence: 99%
See 2 more Smart Citations
“…These precursors have been shown to give a CaO of a very high porosity and surface area [8,9]. Grasa et al [10] reported that the benefit of many of these type of sorbents was significantly reduced under realistic conditions, i.e., higher temperatures and CO2 concentration in the calcination stage, over many cycles. This is likely a result of a very rapid reduction in surface area and porosity, as CaO sinters significantly more rapidly above 900 °C [11].…”
mentioning
confidence: 99%